Cephalic Index of the Northern Bangalore: A Preliminary Study (Indian Internet Journal of Forensic Medicine and Toxicology, 2013)
The cephalic index is the ratio of the maximum breadth of head to its maximum length. Cephalic index is very useful anthropologically to find out racial difference. The present study was carried out on 200 subjects (100 males and 100 females) in Hymanshu Jyothikala Vidyapeetha, Bangalore. The mean cephalic index was 83.5. The mean cephalic index for male was 81.7 and for female was 85.3. Cephalic index of the female is higher than the male. The difference between male and female cephalic index was significant. Majority of the study group were brachycephalic.
Keywords: Cephalic index; head length; head breadth.